2009
DOI: 10.1007/s00018-009-0201-5
|View full text |Cite
|
Sign up to set email alerts
|

Reelin is a platelet protein and functions as a positive regulator of platelet spreading on fibrinogen

Abstract: Abnormalities of platelet functions have been linked to reelin-impaired neuronal disorders. However, little attention has been given to understanding the interplay between reelin and platelet. In this study, reelin was found to present in the human platelets and megakaryocyte-like leukemic cells. Reelin-binding assays revealed that extracellular reelin can interact with platelets through the receptor belonging to the low density lipoprotein receptor gene family. The reelin-to-platelet interactions enhance plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…Reelin, a regulator of brain development and synaptic neuromodulator that signals through ApoE receptors, is also abundant in the liver and present at substantial concentrations in the circulation (21, 23, 24). In the present work, we employed two distinct types of Reelin conditional knockout mice to determine how Reelin affected atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reelin, a regulator of brain development and synaptic neuromodulator that signals through ApoE receptors, is also abundant in the liver and present at substantial concentrations in the circulation (21, 23, 24). In the present work, we employed two distinct types of Reelin conditional knockout mice to determine how Reelin affected atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although atherosclerosis specifically affects arterial vessels, as opposed to the venous system, and is marked by the subendothelial accumulation of lipids and lipid-laden foam cells (40), it shares the recruitment of circulating leukocytes and monocytes to the developing and progressing lesions with other inflammatory processes that involve the vasculature. Reelin has been reported to affect thrombosis and hemostasis (23, 24). Here we have shown that Reelin promotes atherosclerosis by increasing leukocyte adhesion to the vascular endothelium through increased abundance of the major adhesion molecules that are induced during atherogenesis and which promote the accumulation of macrophages in the lesions - ICAM-1, VCAM-1, and E-selectin (34, 35, 41, 42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because they express Reelin [5] and are able to differentiate into lineage‐specific blood cells [19], K562 cells were used in this study to address the role of Reelin in erythroid differentiation. Western blot analysis revealed that the full‐length 420 kDa Reelin protein was elevated by NaB in a dose‐dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%